Long-Term Safety of Intraperitoneal Radio Transmitter Implants in Brown Bears (Ursus arctos) - Arnemo, Jon M.; Ytrehus, Bjørnar; Madslien, Knut; Malmsten, Jonas; Brunberg, Sven; Segerström, Peter; Evans, Alina L.; Swenson, Jon E. (Frontiers in Veterinary Science, 2018)
Intraperitoneal radio transmitters have been widely used in free-ranging wild mammals, but there are no long-term studies on their biocompatibility or technical stability within the abdominal cavity of animals. Possible negative health effects may bias results from ecological studies on instrumented animals and raise concerns over animal welfare issues. The aim of this study was to evaluate the long-term technical stability and pathological effects of Telonics intraperitoneal very high frequency (VHF) radio transmitters in brown bears (Ursus arctos). We instrumented 305 individual bears with intraperitoneal VHF radio transmitters during a 19-year period. We surgically removed devices that had been in bears for 1-9 years and collected transmitters from animals that died 1-13 years after implantation. We took biopsies for histopathology from tissue encapsulating implants in live bears. Retrieved transmitters underwent a technical inspection. Of the 125 transmitters removed from live bears, 66 were free-floating in the peritoneal cavity [a mean (SD) of 3.8 (1.5) years after implantation], whereas 59 were encapsulated in the greater omentum [4.0 (1.8) years after implantation]. Histopathology of biopsies of the 1-15 mm thick capsules in 33 individuals showed that it consisted of organized layers of connective tissue. In one third of the bears, the inner part of the capsule was characterized by a foreign body reaction. We inspected 68 implants that had been in bears for 3.9 (2.4) years. The batteries had short-circuited four (5.9%) of these devices. This resulted in the death of two animals 10 and 13 years after implantation. In two other bears that underwent surgery, we found the short-circuited devices to be fully encapsulated within the peritoneal cavity 5 and 6 years after implantation. A significant proportion of the other 64 inspected implants showed serious technical problems, such as corrosion of metal parts or the batteries (50%), detachment of the end cap (11.8%), and erosion (7.4%) or melting (5.9%) of the wax coating. We conclude that the wax coating of the transmitters was not biocompatible, that the technical quality of the devices was poor, and that these implants should not be used in brown bears.